Analisa Pengaruh Bauran Pemasaran Terhadap Minat Beli Ulang Sepeda Motor Honda Kategori Sport Mid - Eric Kusnadi Kartika (E-Journal Graduate Unpar, 2014)
The growth of the industry motorcycles in Indonesia continues to increase. As more and more brands of motorcycle industry, such as Honda, Yamaha, Suzuki, and others, causing consumers are faced with many alternative brands. Based on the data obtained from PT. Daya Adicipta Mustika as Honda Motorcycles Main Dealer in West Java, it is known that Honda Motorcycles brand has the highest sales volume in the motorcycle industry in Indonesia. However, it is known that there is one category of Honda motorcycle sales volume is still less than its competitors, namely the category Sport Mid (2009-2013), and note that repurchase intention of Honda Sport Mid is still quite low. Proposed research problem to determine the current marketing mix strategy of Honda motorcycles Sport Mid and to determine the marketing mix effect on Honda Sport Mid repurchase intention. In this study used sampling method Non-Random Probability, purposive sampling and testing using Multiple Linear Regression. The survey results revealed Place and Product marketing mix affects the Honda Sport Mid repurchase intention. Meanwhile, based on interviews with PT. Daya Adicipta Mustika, at this time PT. Astra Honda Motor, prefer the Price marketing mix strategies in the Honda Sport Mid marketing. Key Words: Marketing Mix, Repurchase Intention, Honda Sport Mid Motorcycle